(untitled) (Research, Society and Development, 2021)
The present work is a narrative review of the literature to discuss the physical, mechanical, and biological properties of glass ionomer cement (CIVs). To rehabilitate dental units with pathological cavities, the dentist can use several materials to highlight glass ionomer cement, one of the most used oral rehabilitation materials, especially in the primary dentition. Its wide use is associated with the excellent properties of this material, such as fluoride release and absorption, ensuring reduced progression and onset of carious lesions; coefficient of linear thermal expansion similar to the dental structure, drastically reducing the cases of marginal infiltration; adhesiveness in tissues; biocompatibility, so as not to harm the biological tissues of the tooth; acceptable strength and aesthetics when compared to other materials such as zinc oxide and eugenol. To carry out this study, a complete search was carried out in the databases: PubMed, Scielo, Lilacs and Google Scholar, using the keywords “glass ionomer cement, dental materials and dentistry”, inserted in the searches in a cross way adopting the expression boolean " and ”. In order to select the articles to be analyzed, inclusion and exclusion criteria were listed. To ensure restorative success and longevity of ionomer restorations, the professional needs to perform a correct diagnosis and technique so that there is a better use and performance of the properties of that material.